2016
DOI: 10.1186/s13024-016-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

No diurnal variation of classical and candidate biomarkers of Alzheimer’s disease in CSF

Abstract: BackgroundCerebrospinal fluid (CSF) biomarkers have gained increasing importance in the diagnostic work-up of Alzheimer’s disease (AD). The core CSF biomarkers related to AD pathology (Aβ42, t-tau and p-tau) are currently used in CSF diagnostics, while candidate markers of amyloid metabolism (Aβ38, Aβ40, sAPPα, sAPPβ), synaptic loss (neurogranin), neuroinflammation (YKL-40), neuronal damage (VILIP-1) and genetic risk (apolipoprotein E) are undergoing evaluation. Diurnal fluctuation in the concentration of CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…There was a difference between the time of day when samples 1 and 2 were taken. Studies show no diurnal variation in CSF tau levels, [23][24][25] making it improbable that they should fluctuate in the blood significantly during the day. Nevertheless, a representative control group could have ensured that no confounding factors, such as diurnal variation, were responsible for changes in serum tau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a difference between the time of day when samples 1 and 2 were taken. Studies show no diurnal variation in CSF tau levels, [23][24][25] making it improbable that they should fluctuate in the blood significantly during the day. Nevertheless, a representative control group could have ensured that no confounding factors, such as diurnal variation, were responsible for changes in serum tau.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another study on neurosurgical patients showed no diurnal variation in CSF tau levels. 24 Likewise, there was no significant diurnal variation in CSF tau levels among older patients with idiopathic normal pressure hydrocephalus or pseudotumor cerebri, when studied through sequential CSF sampling. 25 Most likely serum tau levels reflect those in CSF.…”
Section: Introductionmentioning
confidence: 85%
“…Some trends suggested herein may prove significant in larger materials. Timing of meals and the time of day for sampling varied, but this is not likely to influence the results, at least regarding tau [ 30 ]. To avoid such limitations, we would like to recommend the HD Clarity project which is a new initiative for a multicenter collection of HD CSF which aims to enroll a large number of participants allowing statistical power for multiple analyses while offering a standardized protocol for CSF collection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sleep deprivation increases amyloid plaque deposition in mice (75). A circadian pattern in the CSF concentration of Aβ has been identified in which Aβ concentration is increased during wakefulness (76), although the magnitude of circadian variation is small and has not been consistently seen (77). The large transfer of fluid from the intracellular to extracellular compartment on wake‐to‐sleep transition, as observed by Xie et al (28), requires a large transfer of solutes (mainly NaCl) into the ECS, and it has been questioned how this can occur (8).…”
Section: Theoretical and Experimental Challenges To The Glymphatic Hymentioning
confidence: 99%